2002
DOI: 10.1088/0953-2048/16/1/201
|View full text |Cite
|
Sign up to set email alerts
|

Progress in melt-processed (Nd Sm Gd)Ba2Cu3Oysuperconductors

Abstract: This comprehensive survey deals with the melt-growth process and characterization of the novel class of ternary materials, (Nd,Sm,Gd)Ba 2 Cu 3 O y 'NSG-123'. Microstructure observations by optical microscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM) revealed the presence of sub-micron secondary phase (RE 2 BaCuO 5 , 211) particles uniformly dispersed in the 123 matrix that enhance flux pinning at low fields and improve the performance of this material. The energy-resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 87 publications
1
29
0
Order By: Relevance
“…It is the short coherence length (≈ 1.5 nm) of YBCO that necessitates nanoscale pinning centers. [34,35] Therefore, a high density of nano-scale defects is needed to provide the flux pinning centers to support the highest possible levels of J c . Recent successes on the introduction of inclusions during pulsed laser deposition (PLD) of YBCO films for enhanced pinning in applied fields by Driscoll et al, and Haugan et al, pointed to a deposition-controlled methodology for addressing this problem.…”
Section: Introductionmentioning
confidence: 99%
“…It is the short coherence length (≈ 1.5 nm) of YBCO that necessitates nanoscale pinning centers. [34,35] Therefore, a high density of nano-scale defects is needed to provide the flux pinning centers to support the highest possible levels of J c . Recent successes on the introduction of inclusions during pulsed laser deposition (PLD) of YBCO films for enhanced pinning in applied fields by Driscoll et al, and Haugan et al, pointed to a deposition-controlled methodology for addressing this problem.…”
Section: Introductionmentioning
confidence: 99%
“…This higher J c of S2 at low temperatures and fields maybe related to the fact that S2 has fine Gd-211 particles in its starting powder, which were the effective pinning centers. 10,11 Whereas in S1 less Gd-211 might be on the precipice. Less Gd-211 phase means saving some Gd ions in S1.…”
Section: Resultsmentioning
confidence: 98%
“…To avoid excessive LRE-Ba substitution, variations of the MTG processes, such as postannealing in Ar atmosphere, using of Barich precursors, and employing large crystallization rate, have been developed. 10,11 In addition, some amount of the LRE 2 BaCuO 5 ͑LRE-211͒ phase are added into the LRE-123 systems to improve the flux pinning. Because GdBa 2 Cu 3 O 7−y ͑Gd-123͒ in the LRE-123 systems shows the slightest Gd-Ba substitution even when fabricated in air, and the "in air" processing will lower fabricating cost, the process of fabricating Gd-123 in air has received much more interests.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the issue of improving J c has been successfully addressed through various methods. In particular, substitution of rareearth elements and addition of a second phase (nonsuperconducting) are very successful and easy methods to improve flux pinning [3][4][5]. Our previous studies have shown that proper quantities of Gd and/or Eu substitution in Y site significantly increased J c .…”
mentioning
confidence: 99%
“…Studies on the effect of Zr addition on J c of (Y, RE)Ba 2 Cu 3 O y thin films showed that the Zr addition can markedly enhance the infield J c values of (Y, Gd)Ba 2 Cu 3 O y films, whereas it reduces that of (Y, Eu, Gd)Ba 2 Cu 3 O y films. 3 (001) single-crystal substrates using trifluoroacetic acid metal organic deposition (TFA-MOD) process. Stoichiometric Y(Eu, Gd), Ba, Cu acetates were dissolved into the mixed solution of deionized water and access trifluoroacetic acid.…”
mentioning
confidence: 99%